Haploidentical Donor Transplantation Using a Novel Clofarabine-containing Conditioning Regimen for Very High-risk Hematologic Malignant Neoplasms. Issue 8 (November 2018) - Sharma, Akshay; Kang, Guolian; Sunkara, Anusha; Inaba, Hiroto; Jeha, Sima; Cross, Shane J.; Geiger, Terrence; Triplett, Brandon
Abstract : Recurrent/refractory hematologic malignancies have a poor prognosis, and there is a need for novel treatment regimens that can be tolerated by this heavily pretreated patient group. Clofarabine has antileukemic activity with an acceptable toxicity profile. In a phase I clinical trial (NCT00824135), we substituted clofarabine for fludarabine in a well-established reduced-intensity conditioning regimen for a T cell–depleted, mismatched-related (haploidentical) donor transplant backbone and explored the maximum tolerated dose of clofarabine in this combination in 15 patients undergoing hematopoietic cell transplantation for recurrent/refractory or secondary leukemia. Clofarabine was well tolerated at a dose of 50 mg/m 2 /d for 5 days in this regimen, with minimal treatment-related mortality in a heavily pretreated group of high-risk patients. All patients exhibited quick hematopoietic recovery, with median times to neutrophil and platelet engraftment being 11 and 16 days, respectively. Transient elevation of transaminases was the most common toxicity—observed in 13 patients (86.7%), with 6 (40%) grade III or above. Three patients (20%) developed hepatic veno-occlusive disease. Eleven patients (73.3%) died, with the most common cause of death being disease relapse (in 9 patients [60%]), followed by treatment-related mortality (in 2 patients [13.3%]). Four (26.6%) of the patients are long-term survivors.